Busyness and speed of work. - Tan, Shu Jing. (2011)
This study examined the relationship between busyness and speed of work. A total of 120 undergraduates participated in the study. Busyness was measured using scrambled sentence task, while speed of work was measured by recording participant‟s timing on a typing task in seconds. Results using a One-way ANOVA demonstrated that there were significant differences between people in the busy, idle and neutral condition. A post hoc comparison using Tukey HSD test only showed significant differences between busy and idle condition, and not between neutral and busy or idle condition. However, there was a correct trend showing that busy people had the fastest timing in completing task, followed by neutral people, and lastly idle people were slowest among three conditions.